2001
DOI: 10.1034/j.1600-0889.2001.530501.x
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse carbon balance of wetlands: methane emission versus carbon sequestration

Abstract: Carbon fixation under wetland anaerobic soil conditions provides unique conditions for long‐term storage of carbon into histosols. However, this carbon sequestration process is intimately linked to methane emission from wetlands. The potential contribution of this emitted methane to the greenhouse effect can be mitigated by the removal of atmospheric CO2 and storage into peat. The balance of CH4 and CO2 exchange can provide an index of a wetland's greenhouse gas (carbon) contribution to the atmosphere. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
178
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(188 citation statements)
references
References 0 publications
6
178
1
2
Order By: Relevance
“…Balancing the greenhouse gas emissions from each of these four marsh types with the short-term carbon accumulation rates may provide a comprehensive understanding of the role of these marshes in overall carbon sequestration (Poffenbarger et al 2011;Holm et al 2016;Krauss et al 2016). For example, fresh marshes may accumulate a large amount of carbon, but they produce methane gas during anaeraboic metabolism, which has a global warming potential that is 25 times greater than carbon dioxide (Whiting and Chanton 2001).…”
Section: Coastwide Tc Short-term Accumulationmentioning
confidence: 99%
“…Balancing the greenhouse gas emissions from each of these four marsh types with the short-term carbon accumulation rates may provide a comprehensive understanding of the role of these marshes in overall carbon sequestration (Poffenbarger et al 2011;Holm et al 2016;Krauss et al 2016). For example, fresh marshes may accumulate a large amount of carbon, but they produce methane gas during anaeraboic metabolism, which has a global warming potential that is 25 times greater than carbon dioxide (Whiting and Chanton 2001).…”
Section: Coastwide Tc Short-term Accumulationmentioning
confidence: 99%
“…The same results were observed in a subarctic peatland in Northern Sweden (Bäckstrand et al 2010). Moreover, if the global warming potential (GWP) of CH 4 and N 2 O is taken into account, many other wetlands could turn into sources of atmospheric radiative forcing (Whiting and Chanton 2001;Friborg et al 2003). Hence, it is necessary to integrate both CH 4 and N 2 O into assessments for the net greenhouse gas (GHGs) effect from wetlands.…”
Section: Introductionmentioning
confidence: 81%
“…CH 4 and N 2 O have 28 and 265 times larger global warming potentials (GWP) than CO 2 over a 100-year timescale, respectively (IPCC 2013). When the GWP of CH 4 and N 2 O are taken into account, many studies have suggested the wetland C sink could be largely offset, and potentially turn into sources of atmospheric radiative forcing (Whiting and Chanton 2001;Friborg et al 2003;Ding et al 2013). In the Carex meadow, soil CO 2 emission dominated the GHG emissions (Table 2).…”
Section: Ch 4 and N 2 O Emissions During Drawdown Periodsmentioning
confidence: 99%
“…The fate of this carbon in a warming climate-i.e., the responses of net carbon balance and CH 4 emissions-is important in predicting climate feedbacks of permafrost thaw. Although northern peatlands are currently a net carbon sink, and have been since the end of the last glaciation, they are a net source of CH 4 (4,5), emitting 0.046-0.09 Pg of carbon as CH 4 per year (4,6,7). Due to CH 4 's disproportionate global warming potential (33× CO 2 for 1 kg CH 4 vs. 1 kg CO 2 at a 100-y timescale) (8), this is equivalent to 6-12% of annual fossil fuel emissions of CO 2 (8.7 Pg of C) (9).…”
mentioning
confidence: 99%